Juridical Analysis of Crimination against Civilizers of Civil Crimination - Sebastian Wibisono; Jawade Hafidz; Ira Alia Maerani (Law Development Journal, 2021)
The formulation of the problem in this research is: What is the process of convicting the perpetrators of criminal acts of detention at the Kendal District Court? What are the obstacles faced by judges in examining and deciding cases of criminal detention at the Kendal District Court and what are the solutions? What is the judge's consideration in deciding criminal cases at the Kendal District Court? The method used by researchers is a sociological juridical legal approach and the specifications in this study include descriptive analytical. Based on the results of research that pThe criminal process for the perpetrators of a criminal act of detention at the Kendal District Court is that the defendant is charged under Article 480 paragraph (1) of the Criminal Code concerning detention. The convictions of the perpetrators of criminal acts at the Kendal District Court in this case the verdict handed down by the Panel of Judges against the defendant was lighter than the charges. Obstacles, namely the imposition of crimes by judges who may be considered lightly by some people in general. The solution is efforts to prevent criminal acts in society, as it is known, the provision of a deterrent effect through the provision of sanctions. Judges' considerations in Deciding Criminal Cases at Kendal District Court are correct, because based on the evidence presented at the trial, it shows that the defendant is found guilty of committing the criminal act of detention and matching all the elements in Article 480 of the Criminal Code. However, the imprisonment imposed by the panel of judges is relatively lighter than the demands of the public prosecutor in which the demands of the public prosecutor are also considered light so that they can provide a deterrent effect on the perpetrators of criminal custody.